Morfological and morfometric study of the ovary in agoutis (Dasyprocta aguti, Linnaeus, 1766) - Almeida, Mônica Marcos de; Carvalho, Maria Acelina Martins de; Cavalcante Filho, Miguel Ferreira; Miglino, Maria Angélica; Menezes, Danilo José Ayres de (Brazilian Journal of Veterinary Research and Animal Science, 2003)
It were studied 24 ovaries belonging to 13 adult agoutis (in two copies it was just researched the left ovary), being 7 pregnant and 6 not pregnant, coming of the "Núcleo de Estudos e Preservação de Animais Silvestres", of the Federal University of Piauí. The organs were described in loco, measured, submitted to section and observed in Optical Microscope. The ovaries, ellipsoids, were located in the sub-lumbar area, flow to the kidneys, flat, with external surface evidencing small transparent areas and the margin mesovarian and lateral face coming covers for the mesossalpinge (ovaric bag). For the right ovary, was observed on the average: weight - 0,082g; length - 0,83cm; width - 0,49cm and thickness - 0,24cm; the left ovary: weight - 0,058g; length - 0,74cm; width - 0,45cm and thickness - 0,23cm. Histologically, this gonads were correspondents with the majority of the rodents sexually actives studies, showing epithelium of simple cubic coating, the outlying cortex and the central medulla (constituted basically by conjunctive slack tissue mixed with vases of blood). In the pregnant females it was counted two to three great central luteous bodies and many other smaller. In the not pregnant the luteous bodies was smaller and more numerous. The cortex is rich in cellular types of conjunctive nature and follicles in different phases of the maturation, which migration of the mesovarian margin for the tubaric extremity, as they increase of size. It was conclued that the ovaries of the agoutis, macro and microscopically, coming the pattern observed in the others rodents actives sexually.